Effectiveness of Chest Physical Therapy in Improving Quality of Life and Reducing Patient Hospital Stay in Chronic Obstructive Pulmonary Disease - Waleed Khan; Aatik Arsh; Syed Muhammad Hammad; Syed Arif Shah; Shahid Khan; Abdul Haq (Journal of the Dow University of Health Sciences, 2018)
Objective: To find out the effectiveness of chest physical therapy along with standard medical treatment versus standard medical treatment alone in improving quality of life and reducing patient's hospital stay in Chronic Obstructive Pulmonary Disease (COPD) patients.